Rhinobatos austini n. sp., a new species of guitarfish (Rhinopristiformes: Rhinobatidae) from the Southwestern Indian Ocean - Ebert, David A.; Gon, Ofer (Zootaxa, 2017)
Rhinobatos austini sp. n. is described from the southwestern Indian Ocean based on four specimens collected from the KwaZulu-Natal Province, South Africa and from Mozambique. The new species, with one exception, can be distinguished from all other members of this genus by a prominent teardrop-shaped dark blotch on the ventral surface of its snout. Its closest congener, R. holcorhynchus, also has a prominent teardrop-shaped blotch on its snout, but the new species differs from it by a lack of prominent thorns and tubercles on it dorsal disc surface and a very striking dorsal surface colour pattern of paired spots, some forming darker transverse bands across its back. Geographically, these two species broadly overlap, but R. austini appears to be a shallow, more coastal species (<1–107 m) compared to R. holcorhynchus that has a mostly offshore (75–254 m) depth distribution.